PCNA ubiquitination-independent activation of polymerase η during somatic hypermutation and DNA damage tolerance - Krijger, Peter H.L.; van den Berk, Paul C.M.; Wit, Niek; Langerak, Petra; Jansen, Jacob G.; Reynaud, Claude-Agnès; de Wind, Niels; Jacobs, Heinz (DNA repair, 2011)
► Polη can be activated dependent and independent of PCNA-Ub during both SHM and DDT. ► PCNA-Ub and Polη are necessary, but not essential, for efficient DDT of UV-lesions. ► PCNA-Ub/ Polh independent DDT of UV-lesions involves Rev1 and Rev3. The generation of high affinity antibodies in B cells critically depends on translesion synthesis (TLS) polymerases that introduce mutations into immunoglobulin genes during somatic hypermutation (SHM). The majority of mutations at A/T base pairs during SHM require ubiquitination of PCNA at lysine 164 (PCNA-Ub), which activates TLS polymerases. By comparing the mutation spectra in B cells of WT, TLS polymerase η (Polη)-deficient, PCNA K164R-mutant, and PCNA K164R;Polη double-mutant mice, we now find that most PCNA-Ub-independent A/T mutagenesis during SHM is mediated by Polη. In addition, upon exposure to various DNA damaging agents, PCNA K164R mutant cells display strongly impaired recruitment of TLS polymerases, reduced daughter strand maturation and hypersensitivity. Interestingly, compared to the single mutants, PCNA K164R;Polη double-mutant cells are dramatically delayed in S phase progression and far more prone to cell death following UV exposure. Taken together, these data support the existence of PCNA ubiquitination-dependent and -independent activation pathways of Polη during SHM and DNA damage tolerance.